Respostas
respondido por:
0
B) x+y = 7 x+y = 7
4/x-2 = 6/y => 6·x + 6·(-2) = 4·y =>
x+y = 7 · (4) => 4x+4y = 28
6x-4y = 12 6x-4y = 12 =>
10x+0y = 40
x = 40/10
x = 4
x+y = 7 => 4+y = 7 => y = 3
C) x/x+y = 1/3 => 1·x+1·y = 3·x
4/x-y = -2 => -2·x -2·(-y) = 4 =>
-2x+y = 0 ·(-1) => 2x-y = 0
-2x+2y = 4 -2x+2y = 4 =>
y = 4 ;
-2x+y = 0 => -2x+4 = 0 => -2x = -4 ·(-1)
2x = 4 => x = 2
4/x-2 = 6/y => 6·x + 6·(-2) = 4·y =>
x+y = 7 · (4) => 4x+4y = 28
6x-4y = 12 6x-4y = 12 =>
10x+0y = 40
x = 40/10
x = 4
x+y = 7 => 4+y = 7 => y = 3
C) x/x+y = 1/3 => 1·x+1·y = 3·x
4/x-y = -2 => -2·x -2·(-y) = 4 =>
-2x+y = 0 ·(-1) => 2x-y = 0
-2x+2y = 4 -2x+2y = 4 =>
y = 4 ;
-2x+y = 0 => -2x+4 = 0 => -2x = -4 ·(-1)
2x = 4 => x = 2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás